PB20 液晶性環状アゾベンゼンの光機能(化学・材料,ポスター発表,2012年日本液晶学会討論会) - 吉田, 勝; 秋山, 陽久; 則包, 恭央; 中村, 優美子; 内田, 江美; 榊, 浩司; 平井, 友樹; 阿澄, 玲子 (Proceedings of Japanese Liquid Crystal Society Annual meeting, 2012)
We have reported on materials that show reversible photoinduced solid-liquid phase transition at room temperature; macrocyclic compounds possessing several azobenzenes in a backbone and alkoxy groups as side chains exhibit excellent photoresponsivity for change from crystal state to liquid state and stability of liquid state. Herein we report the thermal properties, photoisomerization, phase transition and molecular orientation of these liquid-crystalline cyclic azobenzene derivatives.